Sebaran Topik Skripsi Mahasiswa Prodi Strata Satu (S1) Ilmu Perpustakaan Fakultas Ilmu Pengetahuan Budaya Universitas Indonesia 2013-2017 - Faturrahman, Muhammad Ashr; Wijayanti, Luki (UI Scholars Hub, 2020)
This study aims to figure out the tendency of FIB UI Library and Information Science students in choosing their research locus and topics to complete the final project during the period 2013-2017. This research also aims to get an idea of the pattern of locus research selection and research topics. The data used is the thesis of FIB UI Library and Information Science Department students in the 2013-2017 period. This study uses a descriptive method with a quantitative approach. The results showed that students tended to choose loci other than information centers or information institutions such as libraries, archive centers, and record centers, through other sources such as museums, films, novels, social media, information dissemination, and people as objects of research by examining knowledge, behavior, and perspective. The advancement of technology and information media, and scientific development has led to more and more research loci and topics that can be explored, and not limited to topics related to information centers or information institutions, but it can extend to an information culture in a society. On the other hand, research topics related to facilities and services as well as management of an information center or information institution are also widely discussed by Library and Information Science Department students, Faculty of Humanities UI. With this research, it is expected to be able to provide an overview of current trends of research topics in Library and information science.